2022
DOI: 10.1007/s00192-022-05094-9
|View full text |Cite
|
Sign up to set email alerts
|

The subjective and objective very long-term outcomes of TVT in the COVID era: A 20-year follow-up

Abstract: Introduction and hypothesis Few studies in literature have assessed the long-term durability and mesh-related complications of mid-urethral slings (MUSs). The aim of this study is to assess the efficacy and safety of retro-pubic tension-free vaginal tape (TVT) 20 years after implantation for the treatment of female stress urinary incontinence (SUI). Methods A prospective observational study was conducted in two urogynaecologic units in two countries. All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
3
10
0
1
Order By: Relevance
“…As previously reported at the 3-year follow-up [ 9 ], the trend of de novo OAB was significantly increased at the final 5-year evaluation. The rate of the onset of de novo OAB did not differ from the traditional MUSs [ 2 , 3 , 29 ], and it is comparable with previous published data on the TVT-A [ 27 ]. Although we know that antimuscarinic treatment of patients with de novo OAB after MUS implantation is associated with lower efficacy [ 19 ], in our series, patients who started an antimuscarinic treatment for de novo OAB seemed to respond slightly better than with TVT-O [ 29 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As previously reported at the 3-year follow-up [ 9 ], the trend of de novo OAB was significantly increased at the final 5-year evaluation. The rate of the onset of de novo OAB did not differ from the traditional MUSs [ 2 , 3 , 29 ], and it is comparable with previous published data on the TVT-A [ 27 ]. Although we know that antimuscarinic treatment of patients with de novo OAB after MUS implantation is associated with lower efficacy [ 19 ], in our series, patients who started an antimuscarinic treatment for de novo OAB seemed to respond slightly better than with TVT-O [ 29 ].…”
Section: Discussionsupporting
confidence: 87%
“…Our findings suggest that TVT-A is a safe and highly effective procedure for the treatment of SUIs, even in mid-term and long-term follow-up. Although not statistically significant, there seemed to be a slight trend of efficacy reduction with time (from over 95 to 84–88%), and the long-lasting benefits seem to be slightly lower than traditional MUSs (TVT, TVT-O) [ 2 , 3 , 29 ]; however, more studies with a large sample size are needed to demonstrate this.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In our opinion, clinicians should utilize UDS whenever it can improve understanding of the pathophysiology of urinary dysfunction and thereby guide management decision‐making. Urodynamics also enables clinicians to provide informed explanations to patients about the underlying cause of their symptoms 29,30 Unfortunately, over the last 2 years, the use of urodynamics – like other urological and urogynecological interventions – has been dramatically impacted by the COVID‐19 pandemic 31 . We anticipate that the absence of urodynamic assessment will have heightened the chances of misdiagnosis and inappropriate management decisions, especially in “complicated patients,” a daunting problem that we will have to face in the coming years.…”
Section: Discussionmentioning
confidence: 99%
“…Braga et al conducted a 20-year follow-up after TVT surgery and found long-term complications, such as mesh exposure (6.3%), de novo urge incontinence (6.9%), and recurrence (12.5%). They emphasized the importance of early detection and treatment intervention through regular symptom assessment and cystoscopy [ 54 ]. Khanuengkitkong et al reported a case of mesh exposure 10 years after TVT surgery and stressed the need for regular follow-up, even in asymptomatic cases [ 55 ].…”
Section: Reviewmentioning
confidence: 99%